Focus on Brain Angiotensin III and Aminopeptidase A in the Control of Hypertension. (26th June 2012) - Wright, John W.; Mizutani, Shigehiko; Harding, Joseph W.
Abstract : The classic renin-angiotensin system (RAS) was initially described as a hormone system designed to mediate cardiovascular and body water regulation. The discovery of a brain RAS composed of the necessary functional components (angiotensinogen, peptidases, angiotensins, and specific receptor proteins) independent of the peripheral system significantly expanded the possible physiological and pharmacological functions of this system. This paper first describes the enzymatic pathways resulting in active angiotensin ligands and their interaction with AT1, AT2, and mas receptor subtypes. Recent evidence points to important contributions by brain angiotensin III (AngIII) and aminopeptidases A (APA) and N (APN) in sustaining hypertension. Next, we discuss current approaches to the treatment of hypertension followed by novel strategies that focus on limiting the binding of AngII and AngIII to the AT1 receptor subtype by influencing the activity of APA and APN. We conclude with thoughts concerning future treatment approaches to controlling hypertension and hypotension.